1992
DOI: 10.1111/j.1467-6494.1992.tb00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Big Five in Adolescence: Personality and Adjustment during a Developmental Transition

Abstract: The present study probed the links among Big Five personality differences, self-reported personality differences, and adjustment to school among young adolescents. We used a multimethod converging analysis, with three sources of data: (a) adolescent self-report on standardized personality inventories; (b) classroom teacher trait ratings and evaluations of adjustment; and (c) school guidance counselor evaluations of adjustment. Evaluations of adolescent adjustment were systematically related to Big Five persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
1
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 20 publications
5
109
1
4
Order By: Relevance
“…In a similar study, van Aken and Heutinck (1998) found that teacher ratings of low agreeableness at ages 7, 10, and 12 predicted antisocial behaviour at age 20. In several other studies on agreeableness, Graziano and colleagues (Graziano & Ward, 1992;Jensen-Campbell & Graziano, 2001) found that this factor was related to processes and outcomes during interpersonal conflicts, and also to teacher-rated school adjustment. Shiner (2000) found that in 8-12 year olds a higher order factor agreeableness (a combined parent and child description) was related to concurrent rule-abiding conduct (combined peer and parent judgments) and peer nominations on social competence.…”
mentioning
confidence: 99%
“…In a similar study, van Aken and Heutinck (1998) found that teacher ratings of low agreeableness at ages 7, 10, and 12 predicted antisocial behaviour at age 20. In several other studies on agreeableness, Graziano and colleagues (Graziano & Ward, 1992;Jensen-Campbell & Graziano, 2001) found that this factor was related to processes and outcomes during interpersonal conflicts, and also to teacher-rated school adjustment. Shiner (2000) found that in 8-12 year olds a higher order factor agreeableness (a combined parent and child description) was related to concurrent rule-abiding conduct (combined peer and parent judgments) and peer nominations on social competence.…”
mentioning
confidence: 99%
“…attainment and maintenance of relationships, whereas persons low on Conscientiousness have problems with achievement (Barbaranelli et al, 2003;Shiner & Caspi, 2003) and school adjustment (Graziano & Ward, 1992). However, individual characteristics are not the sole determinants of adjustment to the environment.…”
mentioning
confidence: 99%
“…The Big Five dimensions of Extraversion, Agreeableness, Conscientiousness, Emotional Stability (vs. Neuroticism), and Openness to Experience (hereafter Openness) account for the interrelations among most trait terms (Goldberg, 1993b), and they are conceptualized at the broadest level that retains descriptive utility (John, Hampson, & Goldberg, 1991). Possibly because of this breadth, the Big Five are relatively consistent over the life course (Roberts & DelVecchio, 2000), generalize across many different cultures (McCrae & Costa, 1997), and predict a wide range of outcomes including job performance (Barrick & Mount, 1991), academic achievement (Robins, John, & Caspi, 1998), delinquency (John, Caspi, Robins, Moffitt, & Stouthamer-Loeber, 1994), personality disorders (Costa & Widiger, 1994), adjustment (Graziano & Ward, 1992), and divorce (Cramer, 1993). Connecting self-esteem to the Big Five will provide a basis for making predictions about how self-esteem might relate to the same set of outcomes and perhaps even offer clues to the mechanisms linking the Big Five to these outcomes.…”
mentioning
confidence: 99%